Shipping innovation - Wijnolst, Niko (IOS Press, 2013)
Part I: Shipping and the global economy This part sets the scene for understanding the importance of shipping and seaborne trade within the global economy as well as the long-term competitive advantages that countries attempt to establish and how they may succeed and fail in shipping and shipbuilding.